Comparing Dissociative Identity Disorder (DID) Portrayed in Sidney Sheldon’s Tell Me Your Dreams and Alice Jamieson’s Today I Am Alice Nine Personalities, One Tortured Mind - Jessika Kristi (LingPoet: Journal of Linguistics and Literary Research, 2020)
This article attempts to compare two literary works from two different nations with similar motifs, which is Dissociative Identity Disorder. Through a comparison, this study attempts to find out the portrayal of Dissociative Identity Disorder to the main characters and the similarities or differences regarding the issue of Dissociative Identity Disorder that the main characters are suffering from Mental Disorders (DSM-V). The results of the analysis show similarities and differences regarding Dissociative Identity Disorder that is experienced by the two main characters of both literary works, Ashley has 3 of the 6 symptoms of Dissociative Identity Disorder while Alice experiences all six